(3bhd aj JUMjM eSGFd GdLHQ HGdHQGgjf GdgfOSjIs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI bGd GdCUhd GdJj EdjgG QLY CcKQ eSGFd GdLHQ GdKdGKI s
(3BNQgG (B:s
(3hEPG VQHfG aj eKdg cGf eQHY eYdhekG hgh Gdedd , hPdc eG CQOfG Cf s
(3Vef eLehY , JQJjHgG (B: 28s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs